A successful treatment of necrotizing fasciitis following the surgery of distal radius plate removal: A case report and literature review. Issue 15 (April 2018) - Cai, Yuchen; Gan, Yaokai; Yu, Chao; Tang, Jian; Sun, Yuehua
Abstract: Rationale: Necrotizing fasciitis (NF) is defined as a rare, rapidly progressive, and highly lethal skin infection characterized by necrosis of the fascia and subcutaneous tissue. Patient concerns: The present study aims to discuss the case of a 35-year-old man who developed NF following a routine sterile right distal radius bone plate removal surgery. Diagnoses: The patient was suspected of NF based on his clinical manifestations, laboratory tests, and imaging results. The diagnosis of NF was confirmed by histological examinations. Interventions: Serial prompt and extensive debridement was performed during the rapid and aggressive extension of the skin infection, together with antibiotics and supportive treatments. Outcomes: The condition of the patient finally improved on the sixth day of disease progression. Skin grafting of his right forearm wound was performed successfully 2 months after the admission. Lessons: NF can occur during the perioperative period for routine clean radius plate removal operation in patients with no risk factor for NF. The objective is to remind the physicians to stay aware of this disease, especially its early clinical signs and symptoms. Urgent subsequent treatment, including surgical debridement, antibiotic therapy, and supporting management, is the key to ensure the survival and better prognosis of patients.